2020
DOI: 10.1155/2020/5283284
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of the Sciatic Nerve in Streptozotocin-Induced Diabetic Rats with Peripheral Neuropathy

Abstract: Aims. To investigate the candidate biomarkers and molecular mechanisms involved in the early phase of experimental diabetic peripheral neuropathy (DPN). Methods. Diabetes in Sprague-Dawley rats was induced with streptozotocin (STZ) treatment, followed with neurological tests and histological examinations to assess the neuropathic symptoms of DPN. Microarray was performed on the sciatic nerve tissues from control rats and DPN rats at then6th week after diabetes induction, and differentially expressed genes (DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Schwann is sensitive to insulin and glucose concentrations, and Schwann cell dysfunction is implicated in the development of DPN [4]. A previous study showed that KLF11, a diabetesrelated transcription factor, was downregulated in rats with diabetic peripheral neuropathy [8]. The effect of KLF11 on Schwann cells was investigated, and it was discovered that high glucose treatment reduced Schwann cell viability and promoted cell apoptosis [9], and high glucose-treated Schwann has been used as model of DPN [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwann is sensitive to insulin and glucose concentrations, and Schwann cell dysfunction is implicated in the development of DPN [4]. A previous study showed that KLF11, a diabetesrelated transcription factor, was downregulated in rats with diabetic peripheral neuropathy [8]. The effect of KLF11 on Schwann cells was investigated, and it was discovered that high glucose treatment reduced Schwann cell viability and promoted cell apoptosis [9], and high glucose-treated Schwann has been used as model of DPN [9].…”
Section: Discussionmentioning
confidence: 99%
“…KLF11 repressed gluconeogenesis and reduced cellular glucose output, thereby improving hyperglycemia and glucose intolerance in diabetic mice [7]. Moreover, KLF11 expression was downregulated in sciatic nerve tissues of streptozotocin-stimulated diabetic peripheral neuropathy rats [8]. Therefore, it has been hypothesized that KLF11 is involved in the pathogenesis of DPN.…”
Section: Introductionmentioning
confidence: 99%
“…The decline in NPY level was also evident in the spinal nerve roots of the rats in the treated area of DRG, which was associated with some degrees of spinal cord dystrophy. An earlier study has demonstrated increased volume and number of sprouting nerves subsequent to moderate intensity exercise in experimental rats [22]. Also, other studies have demonstrated that exercise has led to the adaptation, increased motor units and innervation of the muscles involved in exercising [23].…”
Section: Effect On Npy Levelmentioning
confidence: 96%
“…Although there is no experimental data available on the effect of nano-eugenol combined with concurrent exercise in experimental animals, our preliminary findings suggest that nano-eugenol provided and enhanced the level of antioxidant support such that neuronal damages due to diabetes could be reduced, repaired or prevented in experimental animals. In this context, further research is warranted to establish the cellular and molecular mechanisms by which the combination of aerobic exercise and nano-eugenol supplementation inhibit the destructive effects of diabetes in animal and human models [22,23].…”
Section: Effect On Npy Levelmentioning
confidence: 99%
“…A study reported that elevated spinal cord area index (SCAI) through upregulation can reduce the development of DPN by inhibiting the Wnt/β-catenin pathway upregulation [53]. This study suggested that targeting the SCAI signaling may be an alternative approach for treating DPN [53].…”
Section: Neuropathymentioning
confidence: 99%